2020
DOI: 10.1108/jpbm-08-2019-2540
|View full text |Cite
|
Sign up to set email alerts
|

Brand equity and customer satisfaction: a comparative analysis of international and domestic tourists in Vietnam

Abstract: Purpose This paper aims to examine the relationships between brand equity, customer satisfaction and cultural distance for a tourism destination. The mediating role of customer satisfaction and the moderating effect of cultural distance in these relationships are assessed. Design/methodology/approach The direct–indirect–moderating relationships were assessed by applying covariance-based SEM (CB-SEM), mediating and multi-group analysis. A paper survey was used to collect data from 618 tourists (domestic and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 104 publications
3
36
1
3
Order By: Relevance
“…A fair indication (27.9%) to post-visitor stays were indicated for longer than 5 days after the event which show potential interest from event visitors in tourism products and destination offerings. What is more, variables relating to repeat visits/ revisiting intentions and promoting the destination to others scored favourably (above 50%) across sport event visitors which further translate to brand equity/ value (Tran et al, 2020;Chi et al, 2020). For the destination to fully realise (long-term) benefits from sport tourism, secondary motivations thus need to be stimulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fair indication (27.9%) to post-visitor stays were indicated for longer than 5 days after the event which show potential interest from event visitors in tourism products and destination offerings. What is more, variables relating to repeat visits/ revisiting intentions and promoting the destination to others scored favourably (above 50%) across sport event visitors which further translate to brand equity/ value (Tran et al, 2020;Chi et al, 2020). For the destination to fully realise (long-term) benefits from sport tourism, secondary motivations thus need to be stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for tourist destinations that offer similar tourism products and possess comparable destination characteristics. In consideration of the foregoing, emerging literature focusses on the empirical investigation of brand equity based on consumer satisfaction and travel (re-visit) intentions (Chi, et al, 2020;Indrie et al, 2020;Tran et al, 2020).…”
Section: Literature Review Brand Positioning In Context To Destinationsmentioning
confidence: 99%
“…TS contributes to DBL and is expressed by re-visitation or recommendation to others (Buhalis et al, 2020;Cakici et al, 2019). Studies (Tran et al, 2020) have confirmed a relationship between TS and DBL. Therefore, the following hypothesis is proposed:…”
Section: Direct Effectsmentioning
confidence: 96%
“…Self-congruity has been demonstrated to be an important factor affecting TS (Kumar, 2016;Kim and Thapa, 2018;Ranjbarian and Ghaffari, 2018). Studies have also evaluated the positive influence of PDQ on tourist contentment (Tran et al, 2020;Wang et al, 2017). Therefore, the following hypotheses are proposed: H2.…”
Section: Direct Effectsmentioning
confidence: 99%
“…However, as the last dimension has no direct relationship with customers’ brand cognition, it is often ignored in marketing research (Lu et al , 2015). Therefore, subsequent scholars mostly proposed different classification methods in the foundation of the four brand equity dimensions given by Aaker (1991), according to different research contexts and business types (Tran et al , 2021; Bose et al , 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%